Is there evidence for a Congo peafowl (Afropavo congensis) in the Middle Stone Age of South Africa? - Comments on Stidham (2008) - A. Manegold; A. Louchart (South African Journal of Science)
Recently, a fossil Congo peafowl (Afropavo congensis) was described from Middle Stone Age Plovers Lake Cave, South Africa.1 Because this species is now restricted to rainforests in the Congo Basin, it was concluded that the fossil indicates forested, or even rainforest, habitats in the vicinity of Plovers Lake Cave during the Pleistocene.1 The correct identification of the fossil specimen is, however, questionable, and the hypothesis of densely forested areas in this area 71 000 years ago is at odds with manifold evidence that grasslands and open woodlands predominated the palaeoenvironment in Pleistocene southern Africa.